(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
In order to survive, grow and develop in conditions of fierce competition, companies on the market inevitably struggle to acquire and take over market share. By taking a significant market share, companies provide security in terms of generating revenue that one market can generate. Different relations between companies in one market in terms of market share primarily determines the level of market concentration. The level of market concentration can vary depending on the market shares of the company from perfect competition, through oligopolies, to a monopoly market. Different levels of market concentration can positively or negatively affect the position and relations between consumers and suppliers, and it is necessary to continuously monitor and analyze the level of market concentration. The aim of this paper is to present, from a methodological point of view, various methods of measuring the level of market concentration, such as the concentration index, the Herfindahl-Hirschman index and the Hall-Tideman index. In the second part, the practical application of the mentioned methods of market concentration analysis on the example of companies from the tobacco industry in the Republic of Serbia in the period from 2016-2018 will be implemented with respect to the criteria of total assets and income from sales. The results of the research should indicate the character of the market of tobacco producers in the Republic of Serbia from the Methods of market concentration analysis based on data from financial statements aspect of market concentration.